PENINGKATAN HASIL BELAJAR MATEMATIKA DALAM MENYELESAIKAN SOAL CERITA TENTANG PECAHAN MELALUI PENDEKATAN REALISTIK - Patimah; N. Ade Maemunah (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2019)
Improving student learning outcomes in story questions about fractions through realistic approaches to students of MIN 3 Pangandaran. The approach in learning is essentially an effort to restore and enhance learning activities carried out by teachers and students. Approach to learn includes factors that determine the level of success of student learning. Realistic Mathematics Approach is an approach used in the learning of school mathematics carried out by placing the reality and experience of students as the starting point of learning The research method used is descriptive method with the form of research is classroom action research. Based on the results of the study, the average student learning achievement increased. In Cycle I only 64%. After improving the learning cycle II to 72% and the third cycle 79%, the average student learning completeness increased. In the first cycle students who only 26%, had improved learning cycle II increased to 16 students 69% and the third cycle became 20 students 86%, and the average student learning activities increased. In the first cycle students who only 42%, had improved learning the second cycle increased to 73% and the third cycle increased to 82%.